The role of religiosity on the relationship between task complexity, experience and audit judgement - Intan Bunga Pertiwi; Taufikur Rahman (Journal of Islamic Accounting and Finance Research, 2021)
Purpose - The purpose of the study is to examine the effect of task complexity and experience on audit judgment with religiosity as moderator on the auditors of the Inspectorate of Semarang Regency and Salatiga City.Method - The data collection of this research was primary by using a questionnaire. The population in this study were all auditors of the Inspectorate of Semarang Regency and Salatiga City. The selection of samples in this study used the purposive sampling technique and selected 45 auditors. The data was processed using IBM Statistics SPSS version 23. The data analysis in this study included the research instrument test (validity and reliability test), classical assumption test (normality, heteroscedasticity, and multicollinearity test), F-test, t-test, and MRA test.Result - The results showed that task complexity and experience partially had a positive and significant effect on audit judgment. The MRA test showed that religiosity did not moderate the effect of task complexity and experience on audit judgment in the auditors of the Inspectorate of Semarang Regency and Salatiga City.Implication - It is expected that auditors consider the religiosity in making audit judgment.Originality - This research is the first study that uses religiosity as a moderator in the relationship between task complexity and experience on audit judgment.